THE MANIFESTATION OF NON-FORMAL MINANGKABAU LANGUAGE PERSERVATION WITHIN CLOSE RELATION SAKATO COMMUNITY IN YOGYAKARTA - Shintia Dwi Alika (LITERA, 2021)
AbstractIndonesian society is a multilingual and multicultural society that embraces different cultural backgrounds, languages, and regional characteristics. One of the characteristics of regionalism and cultural identity of a tribe is the regional language possessed by a region. It is the regional language that gives distinctive features for its speakers. Minangkabau language is one of the regional languages in Indonesia originating from West Sumatra whose native speakers are Minangkabau tribe. Art Society Sakato is a community that originated from the Minangkabau tribe who is quite active and influential in the city of Yogyakarta. The intimacy between the members of Sakato is very deep because they are very familiar and come from the same region. Therefore, this research is focused in the domain of the sacrifice. Despite being away from his home region Sakato still uses the Minangkabau language in a Javanese tribal community. This makes the researcher interested to research about the preservation of sociolinguistic study language. This research is descriptive qualitative. The data collection method used is the method of referring and interviewing. The form of language defense was analyzed using Miles and Huberman's theory (data collection, data reduction, data presentation and conclusion drawing). Based on the results of data analysis, the form of defense of Minangkabau languages of nonformal variety in the sphere of kekariban in the sakato art community in the city of Yogyakarta in the form of phoneme and morphological.Keywords: language preservation, Minangkabau language, the domain of the sacrifice, sakato, the manifestation of language preservation. WUJUD PEMERTAHANAN BAHASA MINANGKABAU NONFORMAL DALAM RANAH KEKARIBAN PADA KOMUNITAS SAKATO DI YOGYAKARTAAbstrakMasyarakat Indonesia merupakan masyarakat multilingual dan multikultural yang mewadahi perbedaan berbagai latar belakang budaya, bahasa, dan ciri kedaerahan. Salah satu ciri kedaerahan dan identitas budaya dari suatu suku bangsa adalah bahasa kedaerahan yang dimiliki oleh suatu daerah. Bahasa daerahlah yang memberi ciri pembeda bagi penuturnya. Bahasa Minangkabau merupakan salah satu bahasa daerah di Indonesia yang berasal dari Sumatera Barat yang penutur aslinya adalah suku Minangkabau. Komunitas Seni Sakato merupakan komunitas yang berasal dari suku Minangkabau yang cukup aktif dan berpengaruh di Kota Yogyakarta. Kedekatan antaranggota Sakato sangat mendalam karena mereka sangat akrab dan berasal dari satu daerah yang sama. Oleh sebab itu, penelitian ini difokuskan dalam ranah kekariban. Walaupun berada jauh dari daerah asalnya Sakato tetap menggunakan bahasa Minangkabau di tengah masyarakat bersuku Jawa. Hal ini membuat peneliti tertarik untuk meneliti tentang wujud pemertahanan bahasa kajian sosiolinguistik. Penelitian ini bersifat deskriptif kualitatif. Metode pengumpulan data yang digunakan adalah metode simak dan wawancara. Wujud pemertahanan bahasa dianalisis menggunakan teori Miles dan Huberman (pengumpulan data, reduksi data, penyajian data dan penarikan simpulan). Berdasarkan hasil analisis data, wujud pemertahanan bahasa Minangkabau ragam nonformal dalam ranah kekariban pada komunitas seni sakato di Kota Yogyakarta berupa fonologi dan morfologi..Kata Kunci : pemertahanan bahasa, bahasa Minangkabau, ranah kekariban, sakato, wujud pemertahanan bahasa.